2020
DOI: 10.2174/1574888x15666200206104332
|View full text |Cite
|
Sign up to set email alerts
|

Stem-Cell Derived Exosomes for the Treatment of Osteoarthritis

Abstract: : Osteoarthritis (OA) is a common degenerative orthopedic disease with multiple pathologic changes in joints that occurs in large population worldwide. No treatment can reverse the progress of OA. Since exosomes were first reported in 1983, researches have been conducted to explore the mechanisms and therapeutic potential of exosomes in treating OA. Exosomes derived from Mesenchymal stem cells have attracted increasingly attention in tackling disease. This article summarizes the current advances and challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Moreover, the chondroprotective effect of DPSCs-exosomes was achieved through delivering exosomal miR-31 to the treated area. Likewise, several studies have confirmed the significant role of miR-31in treating osteoarthritis [51]. This suggests that exosome-mediated injection of miR-31could play a pivotal role in regulating recipient cells functions and cell-to-cell signals.…”
Section: P R E P R I N Tmentioning
confidence: 80%
“…Moreover, the chondroprotective effect of DPSCs-exosomes was achieved through delivering exosomal miR-31 to the treated area. Likewise, several studies have confirmed the significant role of miR-31in treating osteoarthritis [51]. This suggests that exosome-mediated injection of miR-31could play a pivotal role in regulating recipient cells functions and cell-to-cell signals.…”
Section: P R E P R I N Tmentioning
confidence: 80%
“…The microcryogels can provide the MSCs with such a microenvironment and facilitate natural cell–cell and cell–ECM interactions, which can increase their paracrine secretions and result in a range of effects that are beneficial for cartilage repair, including cell homing, anti-inflammation, and immune regulation 41 43 . Moreover, the microcryogels containing accumulated ECM may better preserve the MSC-secreted exosomes to help suppress OA development 44 , 45 . The microcryogels may also offer physical protection to the MSCs by shielding them from mechanical insult and necrosis during and after cell injection 14 , 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the prevalent application of platelet-rich plasma (PRP) in clinical settings, the development of exosome-based therapies is still preliminary, and studies are largely preclinical. Recent research has gradually demonstrated the therapeutic efficacy of exosomes in musculoskeletal healing [ 17 , 18 ]. Exosomes derived from adipose-derived stem cells (ADSC-Exos), for example, have been shown to promote human rotator cuff healing by inhibiting muscle atrophy and degeneration, while also improving the histological properties of the torn tendon [ 19 ].…”
Section: Molecular Mechanisms Of Exosomesmentioning
confidence: 99%